2014
DOI: 10.1371/journal.pgen.1004236
|View full text |Cite
|
Sign up to set email alerts
|

CYP6 P450 Enzymes and ACE-1 Duplication Produce Extreme and Multiple Insecticide Resistance in the Malaria Mosquito Anopheles gambiae

Abstract: Malaria control relies heavily on pyrethroid insecticides, to which susceptibility is declining in Anopheles mosquitoes. To combat pyrethroid resistance, application of alternative insecticides is advocated for indoor residual spraying (IRS), and carbamates are increasingly important. Emergence of a very strong carbamate resistance phenotype in Anopheles gambiae from Tiassalé, Côte d'Ivoire, West Africa, is therefore a potentially major operational challenge, particularly because these malaria vectors now exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
368
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(389 citation statements)
references
References 64 publications
16
368
0
1
Order By: Relevance
“…Afterward, the development of mosquito DNA microarrays allowed screening for resistance genes based on their differential transcription, leading to the identification of detoxification genes conferring resistance (David et al 2005Strode et al 2008;Vontas et al 2010;Edi et al 2014). However, these screenings focused on differential transcription while genomic changes such as CNVs and polymorphisms were neglected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, the development of mosquito DNA microarrays allowed screening for resistance genes based on their differential transcription, leading to the identification of detoxification genes conferring resistance (David et al 2005Strode et al 2008;Vontas et al 2010;Edi et al 2014). However, these screenings focused on differential transcription while genomic changes such as CNVs and polymorphisms were neglected.…”
Section: Discussionmentioning
confidence: 99%
“…A similar role was suggested for the duplication of the acetylcholinesterase gene (carrying the Ace1 mutation) in the resistance of An. gambiae to carbamates (Edi et al 2014). Although such a mechanism is likely contributing to resistance in mosquitoes, no amplification of genes encoding proteins targeted by insecticides were detected in our study.…”
Section: Gene Amplifications Associated With Pyrethroid Resistancementioning
confidence: 99%
“…many putative genes thought to be involved in pyrethroid resistance . However, by far, the majority of pyrethroid resistance-associated genes belong to the CYP6 family of the CYP3 clan (Edi et al 2014), and the CYP4 family of the CYP4 clan (Reid et al 2014). In contrast, little is currently known about the relationship between the CYP2 clan and insecticide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic resistance occurs via increases in either protein levels or the activity of detoxification enzymes that resist insecticides. For example, esterases (Wu et al 2011), glutathione S-transferases (Lumjuan et al 2011), and cytochrome P450 (CYP or P450; Edi et al 2014) have all been demonstrated to be associated with metabolic resistance. In addition, insecticides induce physiological changes in mosquitoes such as a thickening of the epidermis, which subsequently lowers their permeability to insecticides (Wood et al 2010).…”
mentioning
confidence: 99%
“…Although the use of insecticides since the 1960s has proven to be extremely successful, the rise of insecticide resistance has driven a need for development of novel insecticides and alternative vector control strategies [4][5][6][7] . During 2010, a total of 49 of 63 countries reporting to the WHO indicated the occurrence of insecticide resistance in malaria vectors 1 .…”
Section: Introductionmentioning
confidence: 99%